2013
DOI: 10.1002/jor.22429
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral centroid velocity correlates more consistently with cartilage damage than does contact path length in two ovine models of stifle injury

Abstract: Anterior cruciate ligament (ACL) rupture and/or meniscal injury are known risk factors for post-traumatic osteoarthritis. We tested the hypothesis that increasingly abnormal tibiofemoral centroid path lengths and velocities would correlate with the severity of cartilage damage in injured sheep. Six sheep underwent combined ACL/medial collateral ligament transection (ACL/MCLx), five complete lateral meniscectomy (Mx), and four sham arthrotomy (Sham). Weighted centroids were used to estimate in vivo tibiofemoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Additionally, no previous models have considered the classic case of ACL tear combined with meniscus tears. The majority of previous studies have been either isolated ACL tears [6][7][8][9][10][27][28][29][30][31][32][33] or meniscectomy models [33][34][35][36][37]. Thus, there is a need to develop a model that can accurately represent this combined case.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no previous models have considered the classic case of ACL tear combined with meniscus tears. The majority of previous studies have been either isolated ACL tears [6][7][8][9][10][27][28][29][30][31][32][33] or meniscectomy models [33][34][35][36][37]. Thus, there is a need to develop a model that can accurately represent this combined case.…”
Section: Introductionmentioning
confidence: 99%
“…Increased velocity of contact between the tibia and femur has been correlated with increased rates of articular cartilage degeneration in an ovine model (Beveridge et al, 2013); suggesting that scaffolds to repair ligamentous soft tissue injuries should result in velocities of contact that do not differ significantly from that of the intact knee so as to avoid further cartilage injury. Despite this requirement, no data exists that describes the velocity of directly measured contact in human knees during activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior studies that have indicated a relationship between velocity of tibial-femoral contact and rate of cartilage degeneration (Beveridge et al, 2013), and a relationship between shear stress magnitude and structural organization of cell-seeded scaffolds for articular cartilage defects (Chen et al, 2012), we sought to describe the movement of contact on the tibia. The (X, Y) location of the weighted center of contact (WCoC X , WCoC Y ) for the medial and lateral plateau for each frame of data throughout the gait cycle were computed (see Supplement B & Gee and Wang et al, in review), where X is in the medial-lateral direction and Y is in the anterior-posterior direction.…”
Section: Methodsmentioning
confidence: 99%
“…Recent animal work supports these hypotheses, where centroid paths at the knee were increased after an anterior cruciate ligament transection and reduced after meniscal excision. 5 The authors concluded that the mechanism of cartilage damage may be related to increased magnitude and velocity of surface motion in the anterior cruciate ligament transection model and to increased contact stress in the meniscectomy model. These studies highlight the importance of investigating the superficial and deep cartilage layers separately to understand the knee OA disease process.…”
Section: Discussionmentioning
confidence: 99%